Synchronous video computer-mediated communication in English language teaching. (24th April 2021) - Kessler, Matt; Loewen, Shawn; Trego, Daniel
Abstract: In this series, we explore technology-related themes and topics. The series aims to discuss and demystify what may be new areas for some readers and to consider their relevance for English language teachers.